Mass Transfer Effects on Accelerated Vertical Plate in a Rotating Fluid with First Order Chemical Reaction - Muthucumaraswamy, R.; Dhanasekar, N.; Easwara Prasad, G. (Journal of Mechanical Engineering and Sciences, 2012)
The precise analysis of the rotation effects on the unsteady flow of an incompressible fluid past a uniformly accelerated infinite vertical plate with variable temperature and mass diffusion has been undertaken, in the presence of a homogeneous first order chemical reaction. The dimensionless governing equations are solved using the Laplacetransform technique. The plate temperature as well as the concentration near the plate increase linearly with time. The velocity profiles, temperature and concentration are studied for different physical parameters, like the chemical reaction parameter, thermal Grashof number, mass Grashof number, Schmidt number, Prandtl number and time. It is observed that the velocity increases with increasing values of thermal Grashof number or mass Grashof number. It is also observed that the velocity increases with decreasing rotation parameter Ω.